Challenges Faced by Medical Educators at their Workplace A Qualitative Study - Hassan, Bilqis (International Journal of Pathology, 2019)
Background: Establishing departments of Medical Education with a good team of medical educationists and educators for every undergraduate medical College has become essential to overcome the current educational challenges. It is important for the educationists to strengthen teamwork and develop appropriate leadership to improve the overall health-system performance. Objective: To explore the challenges confronted by the medical educators at their own workplace with the purpose to implement theory into practice. Methodology: A Hermeneutic Phenomenological qualitative study was carried out. A total of nine in depth interviews were recorded from the medical educators, graduated from five different medical Universities of Pakistan. The interviews were transcribed verbatim, analyzed and themes were identified. Results: Three themes that emerged after initial and axial coding were 1. Civilization in medical culture.2 Editing Educational trends craves for didactic leaders.3. Smart educators; a key to success. Conclusion: Appropriate leadership with an effective background of medical education is essential to flourish the new culture of medical education for producing professional doctors.